2019
DOI: 10.1055/s-0039-1691492
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Oxidative Annulation of Pyrrolylalkyl-1H-azoles: Towards the Synthesis of Polyheterocyclic Arenes

Abstract: A highly efficient and regioselective palladium-catalyzed annulation protocol for a series of linear and terminally substituted 1,2- and 1,3-di(heteroaryl)alkanes to the corresponding polyheterocyclic arenes is reported. Herein, intramolecular oxidative coupling involving double C(sp2)–H bond functionalization provides a feasible access to biheteroaryl systems annulated to a six-membered ring. The methodology is not restricted to six-membered annulations and was extended to the synthesis of compounds with a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Table 3. Structures of 5-methylbenzo [4,5] The reaction was found to be of general character. It was shown that aromatic and heteroaromatic substituents did not affect yields of the products ( 6a-i, k-l).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3. Structures of 5-methylbenzo [4,5] The reaction was found to be of general character. It was shown that aromatic and heteroaromatic substituents did not affect yields of the products ( 6a-i, k-l).…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 2. Synthesis of 6-methyl-3-phenylbenzo [4,5]imidazo[1,2-a]pyrrolo[2,1-c]pyrazine and 5a-methyl-3-phenyl-5a,6-dihydro-5H,12H-benzo [4,5]imidazo[1,2-a]pyrrolo[1, 2-d]pyrazine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations